Peran Kepribadian Conscientiousness dan Pola Asuh Otoritatif dalam Perilaku Proaktif Mahasiswa (Jurnal Ilmiah Psikologi MIND SET, 2025)
For most students, college life means facing new challenges, leaving their original family residence, living independently, facing increased learning demands, and managing interpersonal communication. Students need to adapt actively to a new environment or engage in proactive behavior to complete the socialization process well. This is because students' experiences in college, both inside and outside the classroom, will have a significant impact on their success during college and beyond. This study aims to examine the role of conscientiousness personality and authoritative parenting in influencing students' proactive behavior. The population of this study is university students in Indonesia. The sample of this study was 83 students who were selected using a convenience sampling technique. The main hypothesis proposed in this study is that there is a significant role of conscientiousness personality and authoritative parenting on students' proactive behavior. The results of the analysis found that the hypothesis in this study was accepted, namely, there is a significant role between conscientiousness personality and authoritative parenting on student proactive behavior with a contribution of 20.3%. Conscientiousness personality in this study plays the most role in students' proactive behavior, followed by authoritative parenting.